(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses modern forms of teaching foreign languages for students specializing in "Tourism." The active methods of teaching a foreign language include the following: discussions, debates, pairing of projects, role-playing games, imitation models.